Gangguan Jiwa Anak Pada Berbagai Jenjang Pendidikan di Sebuah Kota Industri di Kalimantan - Warsiki, Endang; Basoeki, Lestari; Haniman, Fatirnah; Yuniar, Sasanti (Faculty of Psychology, Universitas Surabaya, 2005)
Lack of experience would hamper early detection of behavioral and emotional disturbances in children. In accordance with the framework of this education and counseling program to health providers in an industrial town in Eastern Kalimantan, a guidance handout was constructed to help teachers detect any suspect cases amongst pupils of Play Groups (PG), Elementary Schools (ES), Secondary Schools (SS), and High Schools (HS) in town. The guidance consist of 15 most common deviations found in the community. The target were 78 schools consisting 14 PG classes, 37 ES classes, 15 SS classes, 12 HS classes, totaling 2,670 students as whole population sample. Four hundred fifty one children (16,9%) were detected as suffering various behavioral or emotional disturbances. Kurangnya pengalaman menghambat deteksi dini kasus-kasus jiwa anak. Dalam rangka pemberian pendidikan dan penyulusan kepada para tenaga kesehatan di sebuah kota industry di Kalimantan Tiur, telah diberikan panduan bagi guru wali kelas untuk memperkirakan gangguan jiwa anak/remaja pada siswa TK s.d. SLTA di kota tersebut. Panduan dibuat unutk mengenali 15 jenis gangguan jiwa anak yang banyak terdapat di masyarakat pada umumnya. Rincian sekolah yang diteliti meliputi: 78 kelas sekolah terdiri atas Taman Kanak-Kanak (TK) , 14 kelas; Sekolah Dasar (SD), 37 kelas; Sekolah Lanjutan Tingkat Pertama (SLTP), 15 kelas; Sekolah Lanjutan Tingkat Atas (SLTA), 12 kelas. Total terdapat 2670 murid sekolah sebagai sampel utuh. Perkiraan gangguan jiwa naka/remaja